Successful Intelligence (Analytical, Practical, Creative) Levels among Gifted Students - Hanifa Hassan yousif; Fawkeia Hassan Radwan; Moaid Ismail Jarjis (Zanco Journal of Humanity Sciences)
The current research aimed at identifying successful intelligence levels and dimensions among Gifted students in the Iraqi Kurdistan region (Erbil, Sulaymaniyah and Duhok) and recognizing differences in the successful intelligence levels attributed to gender and the conservation. The research sample consisted of 233 students from Gifted schools, i.e., 127 male students and 112 female students. A descriptive method was adopted and the successful intelligence test was applied to the research sample. The results showed that the Gifted students are distinguished by an average level of successful intelligence, and the results pointed out that there were no statistically significant differences between males and females in the level of successful intelligence (total degree) and dimensional (analytical and creative)while the results also indicated that there were statistically differences in the practical dimension in favor of females, and the results of the Schiffe test showed that there was a statistically difference in the interest of Gifted students in Sulaymaniyah Governorate. Accordingly, the study arrived at a number of conclusions and introduced a number of recommendations and suggestions.